Child Abuse and Children’s Mental Health: A Case Study of Mbale District - Dean Mushikoma (Uganda Christian University, 2024)
This study focused on assessing the effect of child abuse on the children’s mental health, a case study of Mbale District The Specific objectives are Establishing the Effect of Child Abuse on Children’s Mental Health in Mbale District, finding out the different types of child abuses faced by children in Mbale district and pointing out some of the strategies that has been adopted to overcome child abuse in Mbale district. The study sampled 59 respondents out of a study population of 137 respondents according to Morgan (1970) formula of determining the sample size of the respondents. The respondents included, Parents 110, local leaders 15, and health personnel 10 and 02 district officials. Three studies served as the study’s guideline objectives which included Establishing the Effect of Child Abuse on Children’s Mental Health in Mbale District. According to the discoveries, the Effect of Child Abuse on Children’s Mental Health in Mbale District are; Low self-esteem, Increased fear guilty and blame, Distrust of adults, Mental health disorders such as anxiety and depression, Self-harming and suicidal thoughts, Learning disorders, Violence aggressiveness and criminal behavior, Drug and alcohol abuse and high risk sexual, each of these variables had 100% response from the field. The second research objective dealt with finding out the different types of child abuses faced by children in Mbale. The study noted from the findings that the different types of child abuses faced by children in Mbale are, Physical abuse, Sexual abuse, Emotional abuse, Child neglect, Child alcoholism engagement and Child gambling engagement; each of these variables had 100% response from the field. The third research objective dealt with the strategies that have been adopted to overcome child abuse the building maintenance management practices that can be implemented in Mbale city. According to the findings, the strategies that have been adopted to overcome child abuse are, Child counseling, Provision of basic necessities of life and Care and support that have been adopted to overcome child abuse; each of these variables had 100% response from the field. Conclusions .It can be concluded that the Effect of Child Abuse on Children’s Mental Health in Mbale District are; Low self-esteem, Increased fear guilty and blame, Distrust of adults, Mental health disorders such as anxiety and depression, Self-harming and suicidal thoughts, Learning disorders, Violence aggressiveness and criminal behavior, Drug and alcohol abuse and high risk sexual since each of it had majority percentage of the respondents who agreed at 100%. After discussion and presentation of Data, It can be concluded that the different types of child abuses faced by children in Mbale are, Physical abuse, Sexual abuse, Emotional abuse, Child neglect, Child alcoholism engagement and Child gambling engagement. This is due to high percentage response of 100% on each of these variables from the field. It can be concluded that the strategies that have been adopted to overcome child abuse are; Child counseling, Provision of basic necessities of life and Care and support that have been adopted to overcome child abuse, this is also due to high percentage response of 100% on each of these variables from the field. The Recommendations of the Study The researcher recommends the following steps to be taken so as to end the vise of child abuse in Mbale District. The government should seek to reduce poverty as it was found to be the primary contributing factor to child maltreatment. It can accomplish this by providing microfinance credits to individuals operating small companies. Self-help organizations are another way that parents can better their financial situation. According to the report, local parents encouraged child maltreatment. As result, the government must step up its efforts to stop child abuse in rural areas. In elementary schools, guidance and counseling need to be reinforced. It ought to be applied in counseling students of the drawbacks of child labor, among other things.